Equine neutrophils selectively release neutrophil extracellular traps in response to chemical and bacterial agonists - Sheahan, Breanna J.; Schubert, Alicia G.; Schubert, William; Sheats, M. Katie; Schnabel, Lauren V.; Gilbertie, Jessica M. (Frontiers in Veterinary Science, 2025)
IntroductionNeutrophil extracellular traps (NETs) play a significant role in response to a variety of infectious and inflammatory stimuli in human and veterinary medicine. Although entrapment of bacteria can be an important function of NETs, the exuberant release of DNA and other intracellular molecules has also been negatively implicated in the pathogenesis of different diseases. Thus, NET formation must be tightly controlled and represents an opportunity for therapeutic interventions. Horses are particularly sensitive to bacterial stimuli that have previously been shown to cause NETs in other species, but the species-specific processes that control NET release have not been fully elucidated.MethodsThe purpose of this study was to compare the magnitude of response of equine neutrophils to different chemical and bacterial stimuli, including phorbol 12-myristate 13-acetate (PMA), a calcium ionophore (A23187), Staphylococcus aureus, and Escherichia coli. In addition, we investigated whether ex vivo equine NET formation is controlled by the NADPH-oxidase (NOX) pathway and by autophagy, both of which control NET formation in other species.ResultsWe demonstrated that equine neutrophils produce robust NETs in response to calcium ionophore and E. coli stimuli and produce fewer NETs in response to PMA and S. aureus. Both NOX-dependent and NOX-independent pathways of NET formation were identified in equine neutrophils. Autophagy inhibition altered the mechanics of NET release, by reducing the amount of extracellular DNA stranding.DiscussionThese results provide insight into equine-specific neutrophil biology, which could be key for managing equine diseases such as asthma and laminitis.